PENGARUH FINANCIAL LEVERAGE, PROFITABILITAS, DAN FIRM SIZE TERHADAP TINGKAT UNDERPRICING SAHAM IPO DI BURSA EFEK INDONESIA (BEI): THE EFFECT OF FINANCIAL LEVERAGE, PROFITABILITY, AND FIRM SIZE ON THE LEVEL OF UNDERPRICING - Evitasari, Rista; Nurhadi, Nurhadi (Universitas Riau, 2023)
This study aims to determine and analyze the effect of Financial Leverage, Profitability, and Firm Size on the level of underpricing of shares in companies conducting Initial Public Offerings (IPO) on the Indonesia Stock Exchange (IDX). This study is a quantitative research with a sampling method using a purposive sampling technique. Among the 159 total population, there were only 90 companies that became the research sample because some of the population did not meet the predetermined criteria in determining the sample. This study used multiple linear regression analysis techniques, by testing the F-test and t-test hypotheses. Based on the results of this study indicate that simultaneously the variables of Financial Leverage, Profitability, and Firm Size have a significant effect on the level of stock underpricing. Meanwhile, partially only the Profitability variable has a significant effect with a positive coefficient on the level of underpricing of shares, while the Financial Leverage and Firm Size variables do not have a significant effect on the level of underpricing of shares in companies conducting Initial Public Offering (IPO) on the Indonesia Stock Exchange (IDX) period 2019-2021.